Organic Matter in the Topsoil of Soybean Field Alters Arthropod Diversity and Their Covariation - Akhmad Rizali; Julia Putri Pramudita; Eva Febriyanti; Yolla Frinsiska Rama; Tita Widjayanti (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2019)
The presence of organisms in soil play a pivotal role in the health of a ground ecosystem. Diversity and abundance of soil organisms are mainly influenced by soil characteristics and condition of above-ground habitat. This research aimed to study the diversity of arthropods in topsoil of soybean field and investigate factors that affect the abundance and interaction of dominant arthropods. Field research was conducted in three different locations in Malang District, Indonesia. A sampling of arthropods was focused in the topsoil of soybean fields in the soil surface and below-ground. Results found that three dominant taxa of arthropods in the topsoil of soybean field i.e. collembolan, ants, and mites. Different location of soybean field did not affect the species richness and abundance of the dominant arthropods, except the ant abundance. In contrast, soil strata was altered the abundance of collembolan and mites, but not ants. Based on the GLM (generalized linear model), organic matter had a positive relationship with the abundance of collembolan and ants. The abundance of collembolan and ants also had a relationship with mites, yet not vice versa. In conclusion, organic matter in the soybean field supports not only the abundance of arthropod but also their covariation.